Acceptance and Commitment Therapy on suicidal behavior: a systematic review - Ortas-Barajas, Francisco; Manchón, Javier (Anales de Psicología / Annals of Psychology, 2024)
Suicide has emerged as a pressing global issue affecting both society and public health. In this context, Acceptance and Commitment Therapy (ACT) could prove effective in its approach, supported by evidence of the relationship between certain components of ACT and suicidal behavior. Thus, the present study aims to conduct a systematic review on the efficacy of ACT in suicidal behavior. For this, the PRISMA protocol was followed, using the following databases: PsycInfo, PubMed, Scopus and PsicoDoc. Initially, 108 potentially relevant publications were obtained, 13 of which were finally included in the review. We analyzed study quality using a risk of bias assessment instrument. As a result, statistically significant decreases in suicidal ideation (SI) and suicide risk factors were observed. In addition, some studies indicated statistically significant relationships between increased psychological flexibility and decreased SI. While the data suggested the potential effectiveness of ACT in reducing suicidal ideation (SI), more experimental studies are needed to consider the complexity of suicidal behavior and explore the processes of change involved.